2020
DOI: 10.1108/md-06-2019-0815
|View full text |Cite
|
Sign up to set email alerts
|

Creating for others: linking prosocial motivation and social entrepreneurship intentions

Abstract: PurposeThe purpose of this study is to investigate how individuals' prosocial motivation affects their social entrepreneurship intentions (SEI) through the mediating effect of creativity and the moderating effect of family-to-work support.Design/methodology/approachA questionnaire survey was conducted in the Pearl River Delta region in Guangdong, China, and data were collected from 318 respondents who had rich social work experience. To test the hypotheses, a hierarchical linear regression analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 77 publications
3
13
0
3
Order By: Relevance
“…This underscores the ability of important people in the community to mobilize resources from family, friends, neighbors or businesses which, in turn, prepares them to think about identifying and exploiting social needs (Nsereko, 2020; Lanivich, 2015). A growing literature also identifies individual's creativity and prosocial motivation as important antecedents of SEIs (Birgalia and Kadile, 2017; Yu et al , 2020; Bacq and Alt, 2018) (Table 1).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This underscores the ability of important people in the community to mobilize resources from family, friends, neighbors or businesses which, in turn, prepares them to think about identifying and exploiting social needs (Nsereko, 2020; Lanivich, 2015). A growing literature also identifies individual's creativity and prosocial motivation as important antecedents of SEIs (Birgalia and Kadile, 2017; Yu et al , 2020; Bacq and Alt, 2018) (Table 1).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Shahab et al (2019) found that entrepreneurial selfefficacy positively influences entrepreneurial intention in Korea. Similarly, Yu et al (2020) report a positive relationship between entrepreneurs' creativity and social entrepreneurship intentions in China.…”
Section: Entrepreneurial Intentionmentioning
confidence: 97%
“…This underscores the ability of important people in the community to mobilize resources from family, friends, neighbors or businesses which, in turn, prepares them to think about identifying and exploiting social needs (Nsereko, 2020;Lanivich, 2015). A growing literature also identifies individual's creativity and prosocial motivation as important antecedents of social entrepreneurial intentions (Yu et al, 2020). However, in a recent study, found a positive and significant relation between social support and social entrepreneurial intentions (Seyoum, Chinta and Mujtaba, 2021).…”
Section: Opportunity In Actionmentioning
confidence: 99%